ANALYSIS OF CONSUMER BEHAVIOUR IN THE EUROPEAN POULTRY MEAT MARKET - Vida, Viktória; Szakály, Zoltán (Applied Studies in Agribusiness and Commerce, 2023)
This research has also confirmed that poultry meat is currently in its golden age, not only in our country but also globally. The beneficial physiological effects of poultry meat, its nutritional value (high protein content), and its role in modern nutrition and diets have made it the most popular and ’fashionable’ meat product of our time. Healthiness as a megatrend has favoured the consumption of poultry meat, which has been consumed for decades, and is reflected in the growth in production, trade and consumption. The trend of environmental awareness has also pushed the meat market towards the consumption of poultry meat as it is one of the least environmentally intensive compared to other meat types. Poultry meat is the second most commonly consumed meat in the EU, but in some European countries, it has taken over the overall lead (e.g. Hungary, Cyprus, and the UK). Poultry is not only preferred for its healthiness and low environmental impact, it is also an easy, versatile, quick-to-prepare, cheap source of protein. These advantages are expected to lead to further growth in the future in terms of production, trade and consumption, China, the US, the EU and Brazil dominate the poultry sector.